Life-Of-Mine Ventilation and Refrigeration Planning for Resolution Copper Mine (f7fec8ba-f444-4056-8367-98da9f297180) (The Southern African Institute of Mining and Metallurgy, 2014)
Resolution Copper Mine is planned to be a 2000 m deep panel cave mine with virgin rock temperatures above 80°C in rock with a high crystalline silica content. The planned run-of-mine production rate is 120 kt/day. The project is in prefeasibility evaluation. This paper discusses features of the ventilation system design, which include multiple ventilation shafts with total flow of about 3000 m³/s and both surface and underground refrigeration systems with more than 140 MW total capacity. This will be a very challenging mine to ventilate, but this work has demonstrated that it will be technically achievable with the application of existing technology.